Development of a UPLC-ESI-MS/MS method for the determination of triamcinolone acetonide in human plasma and evaluation of its bioequivalence after a single intramuscular injection in healthy volunteers - Zhao, Pengfei; Qi, Ying (Frontiers in Pharmacology, 2023)
A efficient ultra-performance liquid chromatography-electrospray ionization-tandem mass spectrometry (UPLC-ESI-MS/MS) method was developed to determine triamcinolone acetonide (TA) in human plasma and evaluate its bioequivalence after a single intramuscular injection in healthy volunteers. The internal standard was cortisone acetate (CA). TA and CA were extracted from plasma using ethyl acetate and N-hexane (4:1, v/v), separated on a C18 reverse-phase column with a mobile phase of acetonitrile-water containing 1% formic acid (55:45, v/v), and analyzed by UPLC-ESI-MS/MS. Multiple-reaction monitoring was performed using the transitions m/z 435.4→397.3 for TA and m/z 403.4→163.1 for CA. The range of the calibration curve was linear from 0.53 to 21.20 ng/mL. The lower limit of quantification was 0.53 ng/mL. The intra-and interrun precisions were 3.007% to 9.960% and 3.528% to 11.26%, and the intra-and interrun accuracy ranges were −1.962% to −6.577% and −3.371% to 0.348%, respectively. Matrix effect, extraction recovery, and stability all met the National Medical Products Administration (NMPA)-recommended acceptance criteria for bioassays. The main pharmacokinetic parameters of healthy subjects after intramuscular injection of 80 mg test and reference formulations were as follows: